Liming with dolomite reduces the efficacy of the biocontrol fungus Trichoderma koningiopsis against cabbage clubroot (2015)
Cabbage clubroot is a major constraint for the production of cruciferous species. This research aimed to explore the effect of Trichoderma koningiopsis (as the wettable powder formulated product Tricotec®) and dolomite on the disease and crop growth of cabbage. This study was carried out in a field with a prolonged history of clubroot incidence. The trial was set up in a randomized complete block design with five repetitions. The following treatments were applied: 0) absolute control; 1 and 2) liming with dolomite at 1.0 and 2.1 t ha-1; 3) Tricotec® at 200 g ha-1; 4) combination of treatments 1 and 3; 5) combination of treatments 3 and 4. The treatment with just Tricotec® applications gave the lowest disease incidence and severity and the heaviest plant dry weight. Joint applications of Tricotec® and dolomite at 2.1 t ha-1 reduced the crop growth variables and had the highest disease intensity. The Trichoderma concentration in the soil was increased by a factor of 10 in the plots that received just Tricotec®, but not in the limed plots. These results showed that T. koningiopsis, in a Tricotec® formulation, is a promising candidate for the control of cabbage clubroot and that its biological activity is affected by dolomite when applied jointly at 2.1 t ha-1.